MPN-PCR enumeration of Campylobacter spp. in raw chicken meats and by-products - Yew Huat, John Tang; -, Ghazali; -, F.M.b; -, Saleha (2010)
The goal of this study is to enumerate Campylobacter in chicken meats and by-products. In the current investigation, results showed that raw chicken meats and chicken by-products were contaminated with Campylobacter ranging from <3 to 4600 MPN·g−1. Campylobacter jejuni showed a higher number compared to Campylobacter coli in the chicken samples. The current study showed that the percentage of chicken livers and gizzards harbored a higher number of Campylobacter (103–104 MPN·g−1) than other chicken parts at 33.3% and 9.2%, respectively. The different concentrations of Campylobacter between chicken meats and chicken byproducts reflect the differences in the contamination level. The data on Campylobacter concentration in chicken meats and by-products will be useful in risk analysis. KeywordsMPN-PCR (most-probable-number PCR)- Campylobacter -chicken meats-chicken by-products.